Endogenous money in an era of financialization - Malcolm Sawyer (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2020)
The paper opens with a consideration of the historical developments on the nature and features of money and endogenous money, and the post-Keynesian revival of ideas of endogenous money. Particular attention is drawn to the work of Basil Moore in relation to endogenous money, including the location of that analysis with commercial banks (some of whose liabilities are transferable and widely accepted as a means of payment) and the post-Keynesian-inspired revival of endogenous money. There is a brief outline of the aspects of financialization since the late 1970s which have relevance for the analysis of banks and money. Some thoughts are offered on the impact which those changes of the financial system have for the analysis of banks and of money.
Keywords: E42; E51; G00; 330; financialization; endogenous money; banks; securitization; shadow banks